A high-performance oxygen evolution catalyst in neutral-pH for sunlight-driven CO2 reduction - Li Qin Zhou (Nature Portfolio, 2019)
Solar-to-fuel conversion under mild conditions offers a renewable means to store energy. Here authors report a Brownmillerite oxide for neutral-pH oxygen evolution that, when integrated with an anodized silver cathode, enables a 13.9% energy-conversion efficiency for light-driven CO2 reduction